Completeness Of Nursing Evaluation Documentation In Integrated Patient Development Records In Diabetes Mellitus Patients In A Palembang Hospital - Citra Suraya; Tukimin; Aris Citra Wisuda; Regidor III Dioso (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
Background: Diabetes mellitus is a chronic disease that has increased to 76.77% globally. Patients with diabetes mellitus need continuous Care in the nursing process. Documentation of integrated diabetes mellitus nursing evaluation in progress notes is a communication tool in integrated Care carried out by professional caregivers in providing health services to diabetes patients. Incomplete documentation will form an unfavorable framework that will exacerbate the PPA framework because documentation is essential for the professional practice of doctors, nurses, pharmacists and nutritionists to avoid unexpected events (KTD), medication errors Hospital intervention errors. Objectives: This study looks at the factors that most influence PPA in documenting integrated patient development records in the Inpatient Room of A Hospital Palembang. Research Methods: The research design is a non-experimental or analytic survey with a cross-sectional approach. The research was conducted from April 27, 2023, to May 17, 2023. The population in this study were caregivers consisting of doctors, nurses, pharmacists and nutritionists. The sampling technique for this study was proportional random sampling with a total sample of 72. The data analysis used was Chi-Square. Results: The description of the results of this study shows that the research conducted at Hospital A found Integrated Patient Progress Notes completeness by four professional care providers but incomplete integrated patient progress notes filling was found at 76.4% Conclusion: Obtained incomplete documentation of integrated patient progress notes at Hospital A Palembang.